Model Agromarine Berkelanjutan Melalui Integrasi Teknologi Karamba Jaring Apung (KJA),Rumpon Dasar Ramah Lingkungan dan Sero Sistem Kluster di Sulawesi Tenggara - La Ode Abdul Rajab Nadia; Abdullah Abdullah; Amadhan Takwir (Jurnal Nasional Teknologi Terapan (JNTT), 2018)
Model of agro-marine is a solution for an integrated and sustainable coastal management in coastalcommunities. The contribution of sero in combination with bottom fish aggregating device (FAD) isimportant as the supplier of broodstock and diet for fish reared on floating cages. The objective of thepresent study was to increase aquaculture production sustainably in floating cages and to enhancebroodstock production, feed-fish stock  and fish consumption harvested by sero and FAD in order togenerate integrated business incubation in favor of fish consumption in Southeast Sulawesi. The studywas conducted in Staring Bay, South Konawe Regency, Southeast Sulawesi. This study identifiedbroodstock and consumed fish harvested from sero and FAD, the collection of fish to be stocked infloating cages, broodstock adaptation and fish rearing on floating cages, and fish production to reachmarketable size. Results showed that there were 1,500 broodstock of Caranx sp., harvested from sero,and 180 broodstock of lobster with the size ranges between 200 and 220 g/individual collected bybamboo fishing trap (bubu) placed in FAD. During the study, the survival of  Caranx ignobilis, andlobster reached  between 84.25-88.15% and 92.33%, respectively. The fish were fed fresh trash fishharvested from sero and FAD. The production of fish consumption post harvest ranged from 380.5-560 kg/month. The agro-marine model contributes to an optimal production and minimizes productioncost of aquaculture and also increases fish consumption sustainably.